The Social Cost of Near-Rational Investment - Hassan, Tarek A.; Mertens, Thomas M. (American Economic Review, 2017)
We show that the stock market may fail to aggregate information even if it appears to be efficient, and that the resulting decrease in the information content of prices may drastically reduce welfare. We solve a macroeconomic model in which information about fundamentals is dispersed and households make small, correlated errors when forming expectations about future productivity. As information aggregates in the market, these errors amplify and crowd out the information content of stock prices. When prices reflect less information, the conditional variance of stock returns rises, causing an increase in uncertainty and costly distortions in consumption, capital accumulation, and labor supply. (JEL D14, D83, D84, E21, E22, E24, G14)